Labour regimes and global production - Baglioni, Elena; Campling, Liam; Coe, Neil M.; Smith, Adrian, 1966- (Agenda Publishing Limited, 2022)
The book considers a range of conceptual debates around labour regimes and global production relating to issues of scale, informality, race, social reproduction, the labour process and migration as well as in relation to methods, theory and research practice.
Keywords: Labor movement.; Production (Economic theory); Mouvement ouvrier.; Production.; Labor movement